2017
DOI: 10.3390/ijms19010028
|View full text |Cite
|
Sign up to set email alerts
|

Docosahexaenoic Acid in Combination with Dietary Energy Restriction for Reducing the Risk of Obesity Related Breast Cancer

Abstract: There is strong evidence that obesity poses a significant risk factor for postmenopausal breast cancer. There are multiple mechanisms by which obesity can predispose to breast cancer, prominent among which is the creation of a pro-inflammatory milieu systemically in the visceral and subcutaneous tissue, as well as locally in the breast. Although dietary intervention studies have shown in general a favorable effect on biomarkers of breast cancer risk, it is still unclear whether losing excess weight will lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…However, a diet rich in added sugars (sucrose and fructose) induces a reduction of ω-3 PUFA neuroprotective activity, resulting in increased neuroinflammation, reduced neurogenesis and cognitive deficits [117]. Finally, by combining DHA supplementation with dietary energy restriction, BC-related obesity can be counteracted, for the dual effect on fatty acid metabolism and cell growth pathways, leading to inhibition of cell proliferation and induction of apoptosis; however, the effects in humans have to be proven [118]. Thus, for improvement of patient quality of life, it is possible that EPA and/or DHA will soon be recommended as adjuvants for chemotherapy and radiotherapy in BC patients.…”
Section: Nutritional Interventions During Bc Treatmentmentioning
confidence: 99%
“…However, a diet rich in added sugars (sucrose and fructose) induces a reduction of ω-3 PUFA neuroprotective activity, resulting in increased neuroinflammation, reduced neurogenesis and cognitive deficits [117]. Finally, by combining DHA supplementation with dietary energy restriction, BC-related obesity can be counteracted, for the dual effect on fatty acid metabolism and cell growth pathways, leading to inhibition of cell proliferation and induction of apoptosis; however, the effects in humans have to be proven [118]. Thus, for improvement of patient quality of life, it is possible that EPA and/or DHA will soon be recommended as adjuvants for chemotherapy and radiotherapy in BC patients.…”
Section: Nutritional Interventions During Bc Treatmentmentioning
confidence: 99%
“…Therefore, DHA appears as a safe, natural compound that can greatly improve the anticancer properties of anticancer drugs by additive or synergistic interactions [14,45,46]. In addition, n-3 PUFA reduced the risk of obesity-related breast cancer [47] and had protective effects towards the cardiotoxicity of anthracyclines, the most extensively used chemotherapeutics [48,49]. Thus, current results of cohort studies and investigations in cell lines or animal models demonstrated that DHA could reduce tumor cell number by acting as soon as the cell begins its neoplastic transformation through a decrease in proliferation and an increase in apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Docosahexaenoic acid (DHA) has a high medical and nutritional value; it promotes visual acuity and neural development (Boelen et al 2013 ), and reduces the risk of some diseases such as cardiovascular, arthritis, diabetes, and obesity related breast cancer (Biscione et al 2007 ; Lee et al 2012 ; Manni et al 2017 ). As a result, DHA has received worldwide attention in past decades.…”
Section: Introductionmentioning
confidence: 99%